Cognitive Resources Necessary for Motor Control in Older Adults Are Reduced by Walking and Coordination Training - Godde, Ben; Voelcker-Rehage, Claudia (Frontiers in Human Neuroscience, 2017)
We examined if physical exercise interventions were effective to reduce cognitive brain resources recruited while performing motor control tasks in older adults. 43 older adults (63 to 79 years of age) participated in either a walking (n = 17) or a motor coordination (n = 15) intervention (1 year, 3 times per week) or were assigned to a control group (n = 11) doing relaxation and stretching exercises. Pre and post the intervention period, we applied functional MRI to assess brain activation during imagery of forward and backward walking and during counting backwards from 100 as control task. In both experimental groups, activation in the right dorsolateral prefrontal cortex (DLPFC) during imagery of forward walking decreased from pre- to post-test (Effect size: -1.55 and -1.16 for coordination and walking training, respectively; Cohen’s d). Regression analysis revealed a significant positive association between initial motor status and activation change in the right DLPFC (R² = .243, F(3,39) = 4.18, p=.012). Participants with lowest motor status at pretest profited most from the interventions. Data suggest that physical training in older adults is effective to free up cognitive resources otherwise needed for the control of locomotion. Training benefits may become particularly apparent in so-called dual-task situations where subjects must perform motor and cognitive tasks concurrently.